Waveform distortion and transmission gain on ultra wideband impulse radio - Promwong, Sathaporn; Supanakoon, Pichaya; Takada, Jun Ichi (My University, 2010)
A waveform of an ultra wideband impulse radio (UWBIR) system can be extremely distorted through a channel even for free-space transmission because of antenna dispersion. This highly degrades the link budget performance. Therefore, the understand of antenna characteristics, which effects on waveform distortion, is necessary. This paper studies the waveform distortion due to antenna in free space transmission in UWB-IR system. The link budget is usually evaluated by using the Friis' transmission formula. However, it is not directly applicable to the UWB-IR transmission system. The link budget evaluation formula attended from conventional Friis' transmission formula that takes into account the transmitted waveform, its distortion due to the antennas, the channel and the correlation receiver is proposed. Since the antenna is significant pulse-shaping filters in UWB-IR system, the example kind of the log-periodic dipole antenna (LPDA) is experimentally examined, especially focused on the effect of the template waveforms. Copyright © 2010 The Institute of Electronics, Information and Communication Engineers.
Keywords: Antenna; Distortion; Friis' transmission formula; Transmission gain; Ultra wideband impulse radio (UWB-IR)